2018
DOI: 10.31062/agrom.v25i1.26282
|View full text |Cite
|
Sign up to set email alerts
|

Demanda hídrica da cana-de-açúcar, por balanço de energia, na microrregião de Teresina, Piauí

Abstract: O objetivo deste estudo foi quantificar a demanda hídrica da cana-de-açúcar, por meio do método de balanço de energia (razão de Bowen), na microrregião de Teresina, Piauí. O experimento foi conduzido na Usina COMVAP, na microrregião de Teresina, Piauí. A cultivar utilizada foi a RB867515, irrigada por pivô central. Para a estimativa de evapotranspiração da cultura (ETc) usou-se uma torre equipada com sensores microeletrônicos instalada no centro de um talhão de 10 ha. A evapotranspiração de referência (ETo) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
1
1
2
Order By: Relevance
“…Pearson's correlation, canonical correlation, and Stepwise regression analyses indicated that the most important meteorological variable for the growth and development of sugarcane in the central and northwest regions of the state of Rio Grande do Sul is air temperature, i.e., the ATS. This result differs from those of most studies reported in the literature, in which the main variable that determines the growth and development of sugarcane is precipitation (DIAS et al, 1999;DARLI et al, 2008;LI & YANG, 2014;KUMAR et al, 2016;ANDRADE JUNIOR et al, 2017). However, in the studied regions, the annual precipitation ranges from 1990 mm to 2500 mm, which is 500 to 1000 mm higher than that in the regions where sugarcane is traditionally grown (ALVARES et al, 2013).…”
Section: Resultscontrasting
confidence: 65%
“…Pearson's correlation, canonical correlation, and Stepwise regression analyses indicated that the most important meteorological variable for the growth and development of sugarcane in the central and northwest regions of the state of Rio Grande do Sul is air temperature, i.e., the ATS. This result differs from those of most studies reported in the literature, in which the main variable that determines the growth and development of sugarcane is precipitation (DIAS et al, 1999;DARLI et al, 2008;LI & YANG, 2014;KUMAR et al, 2016;ANDRADE JUNIOR et al, 2017). However, in the studied regions, the annual precipitation ranges from 1990 mm to 2500 mm, which is 500 to 1000 mm higher than that in the regions where sugarcane is traditionally grown (ALVARES et al, 2013).…”
Section: Resultscontrasting
confidence: 65%
“…The irrigation depth was established based on crop evapotranspiration (ETc), using the reference evapotranspiration (ETo) estimated by the Penman-Monteith method, based on daily climatic data from an automatic weather station installed at the site (Embrapa Meio-Norte) and on crop coefficients of sugarcane established for the region (ANDRADE JÚNIOR et al, 2017). The irrigation application frequency was three times a week (Mondays, Wednesdays, and Fridays).…”
Section: Methodsmentioning
confidence: 99%
“…É mais apropriado substituir a palavra consumo pela palavra uso. O consumo traz uma visão equivocada de que a água que passa pelo interior da planta é permanentemente perdida, desaparece do sistema hídrico (ANDRADE JÚNIOR et al, 2018;SANTIAGO et al, 2018). E é um equívoco concluir que a cana-de-açúcar em sistema irrigado, por utilizar água proveniente dos cursos d'água, usa mais água que uma cana de sequeiro.…”
Section: Mito: Cana Sob Sistema Irrigado Consome Mais áGua Do Que Em ...unclassified